Studi Pemanfaatan Rumput Laut (Eucheuma Cottoni) Untuk Bahan Baku Pembuatan Produk Kosmetika - Destiana Putri Fadhillah; Neneng Siti Silfi Ambarwti; Dwi Atmanto (Departement of Mathematics Education, 2024)
Indonesia is an archipelagic country with abundant natural resources and significant potential as a seaweed producer. The types of seaweed that can grow in Indonesia and have economic value include Eucheuma cottonii, Gracilaria sp., Eucheuma spinossum, and Caulerpa sp. Eucheuma cottonii seaweed is a source of carrageenan, which has great potential for use in various fields, both in the food and non-food industries, due to its capabilities as a stabilizer, thickening agent, and emulsifier. This research employs a qualitative descriptive approach, which does not aim to conduct calculations or statistical processes, but rather to describe a situation in depth, thereby providing a well-represented condition. From various literature studies conducted, the author found that Eucheuma cottonii seaweed contains five main components: natural antioxidants, anti-inflammatory agents, antifungal agents, antibacterial agents, and moisturizers. Cosmetic products that can be derived from Eucheuma cottonii seaweed include moisturizing creams, face masks, soaps, lip balms, and face serums..